Learning media and strategies used by english students in practice teaching during the pandemic - Syahdan Syahdan; Herlinawati Herlinawati; Marwa Marwa (Universitas PGRI Semarang, 2021)
Practice teaching, indisputably, is one of the school activities distorted significantly due to the COVID-19 pandemic. Practice teachers should adapt online learning to convey teaching and learning activities. This study aimed at finding out the internet device (wi-fi) available at schools in Pekanbaru municipality and learning media used by practicum teachers with the stable internet connectivity at schools in Pekanbaru municipality. There were 47 out of 51 English Education Students of Universitas Lancang Kuning involved in this research. They filled in 27 items of close-ended questions in the Likert scale. The findings revealed that most schools (83%) had wi-fi devices accessed by practicum teachers for teaching activities. With this device, practice teachers used more diverse applications (Google Classroom, Google Form, and Zoom video conference) more frequently (often), shown in the mean score of 4.0, to convey learning materials and tasks delivery. In schools with unstable internet connectivity, they chose the Whattsapp application to convey learning activities, including the delivery of the tasks. In conclusion, the availability of a wi-fi device with stable internet connectivity supports practice teachers in conducting online teaching activities during the pandemic. They can maximize the use of more diverse applications, namely Google Classroom, Google Form, and Zoom conference